Online college laboratory courses: Can they be done and will they affect graduation and retention rates? - Eddy van Hunnik (Laureate Education Inc, 2015)
Online education has been steadily growing during the last decade. This growth has mainly taken place in the non-laboratory science fields. This essay describes some of the best practices to increase and maintain student retention, increase student engagement and increase graduation rates for college running online laboratory science courses. This article further discusses how to run successful, hands-on laboratory courses for your online students. The most common issues are being discussed and what can be done to provide the students with the same hands-on experience online as what they would experience in a more traditional classroom setting. DOI: 10.18870/hlrc.v5i4.289